Strategi Pengembangan Bisnis Pada UMKM SilverEgg - Sidqi, Alzan Zhafir; Fanji, Fanji Wijaya; Herlinawati, Erna (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
The chicken egg deals industry is confronting many challenges as egg deals play a part within the agribusiness and nourishment division, assembling the protein needs of people and representing one of the foremost predominant businesses worldwide. To make strides in the execution and victory of this industry, numerous businesses are utilizing SWOT investigation. This inquiry about extension is outlined to conduct a SWOT investigation for the chicken egg deals division to pinpoint its qualities, shortcomings, openings, and dangers. The primary research strategy utilized includes conducting field overviews to gather information. The results of this examination shed light on viewpoints such as item quality, competition inside the supply chain, and advancing shopper preferences. With these bits of knowledge, suggested commerce methodologies can be created to promote the execution and success of chicken-egg deals in this commercial center. The SWOT investigation recognizes qualities like tall item quality and highlights shortcomings like dependence on external feed supplies. It, too, distinguishes openings, such as developing requests for items, and dangers like competition within the advertising. Bits of knowledge from field overviews offer data on changing shopper inclinations and impediments confronted by industry players. This consideration provides an examination of advertising conditions. Recommends conceivable strategies to improve the position of the chicken-egg deals segment in this ever-changing showcase scene